2011
DOI: 10.3168/jds.2010-3776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of somatic cell count thresholds to detect subclinical mastitis in Gyr cows

Abstract: The objectives of this study were (1) to determine the sensitivity (Se) and specificity (Sp) of somatic cell count (SCC) thresholds to identify subclinical mastitis in Gyr cows caused by major and minor pathogens; (2) to study the effects of month of sampling, rear or front mammary quarters, herd, intramammary infection (IMI), and bacterial species on SCC at quarter level; and (3) to describe the prevalence of IMI in Gyr cows in commercial dairy herds. In total, 221 lactating Gyr cows from 3 commercial dairy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
5
28
0
Order By: Relevance
“…Almost similar to this result, Malek dos Reis et al, (2011) reported that rear quarter had higher log SCC (5.10) compared with front quarters (5.03). Schepers et al, (1997) also reported a higher SCC in rear quarters.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Almost similar to this result, Malek dos Reis et al, (2011) reported that rear quarter had higher log SCC (5.10) compared with front quarters (5.03). Schepers et al, (1997) also reported a higher SCC in rear quarters.…”
Section: Discussionsupporting
confidence: 76%
“…Most frequently isolated bacteria was staphylococcus aureus (18.33%) which suggests that the prevention of spread of contagious bacteria during milking was not effective. Similar to this, Staphylococcus aureus was the most frequently isolated pathogen in Sweeden (19%), Jordan (22.2%), and Brazil (30.8%) (Persson et al, 2011;Malek dos Reis et al, 2011;Alekish, 2015). Besides other minor pathogens, Staphylococcus aureus was still the most prevalent pathogen in clinically healthy animals and both environmental and contagious forms of mastitis may be caused by Staphylococcus aureus (Rall et al, 2013;Barkema et al, 2009).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Subclinical mastitis is the biggest problem affecting dairy cattle worldwide (MEMON et al, 2013), usually cause a rise in somatic cell counts (SCC) and affect the daily milk production between 15-45% without visible changes to milk itself or the udder (MALEK DOS REIS et al, 2011) furthermore, may occurs expenses with treatment expenses, death or culling of animals.…”
mentioning
confidence: 99%